Transit Time Flow Measurement in Robotic Totally Endoscopic Coronary Artery Bypass: What Do the Numbers Mean?. Issue 2 (March 2022) - Yang, Benjamin; Nisivaco, Sarah; Torregrossa, Gianluca; Balkhy, Husam H.
Objective: Transit time flow measurement (TTFM) is valuable for assessing intraoperative graft patency in coronary artery bypass surgery (CAB). The significance of competitive native coronary flow on patency, as predicted by percentage of backflow (%BF) on TTFM, is unknown. This study aims to evaluate intraoperative TTFM parameters, and specifically %BF, in predicting graft patency in robotic totally endoscopic CAB (TECAB). Methods: We reviewed TTFM parameters in 311 patients undergoing robotic off-pump TECAB at our institution between February 2016 and January 2020. Patients with sequential or Y grafts were excluded, leaving 277 patients with a total of 387 isolated end-to-side grafts (248 left internal mammary artery [LIMA], 149 right IMA [RIMA]). Mean graft flow, diastolic flow, pulsatility index, and %BF were measured intraoperatively. Early postoperative angiograms were obtained in 83 patients undergoing percutaneous coronary intervention for hybrid revascularization, with a total of 125 grafts. Angiograms were independently analyzed and separated into 2 groups based on IMA graft patency, which were patent (FitzGibbon A/B) and nonpatent (FitzGibbon O) groups. Results: Early angiographic patency at a median of 31.0 days after surgery showed 123 (97.1%) patent grafts and 3 (2.9%) occluded grafts in both LIMA and RIMA grafts to both left anterior descending (LAD) and non-LAD targets. Mean graft flow was 77.4 ± 41.6 mL/min. There was no difference in mean flow, pulsatility index, or %BF between the patent and occluded grafts. Conclusions: Excellent intraoperative flow parameters and early angiographic patency can be obtained via robotic, off-pump TECAB. Our data did not demonstrate an association between intraoperative TTFM evidence of competitive native coronary flow and early angiographic graft outcomes.